Multidimensional fixed-point theorems and applications - Akhadkulov, Habibulla; Saaban, Azizan; Akhatkulov, Sokhobiddin; Alsharari, Fahad (2017)
The purpose of this work is to present the applications of multidimensional fixed point theorems. For this, we prove some multidimensional fixed point theorems and then using these theorems we show the existence and uniqueness of solution of a systems of matrix equations.